A Calculating Actual Stature of Elderly through Arm Span and Knee Height Measurements - Julia Pertiwi; Martha Irene Kartasurya; Djoko Tri Hadi Lukmono; Henry Setyawan; Martini Martini (Health Notions, 2018)
-